Visible-driven industrial wastewater remediation using black titania: optimization, energy consumption, treatment, and material preparation costs estimation - Nawaz, Rab; Arshad, Ushtar; Marlia, Mohd Hanafiah; Haider, Sajjad; Anjum, Muzammil; Abdel Baki, Zaher; Khan, Rawaiz; Zaini, Sakawi; Muhammad, Aqif; Haider, Adnan; Sumaiya, Zainal Abidin (Elsevier, 2025)
Herein, black titania nanoparticles (BTNs) were synthesized via chloride sol–gel route which were then employed for the remediation of phenolic compounds (PCs) contaminated wastewater. A total of 2.70 L of input reagents and 28.33 kWh of electrical energy (EE) were required to produce 1 kilogramme of BTNs at a cost of 1231.872 dollars. The performance of BTNs for the degradation of PCs was significantly affected by various reaction conditions, which were optimized at 1.2 g/L of BTNs, 0.04 mol/L of H2O2, 30 mg/L of PCs concentration, and pH of 7.4 using statistical and machine learning (ML) models. Operated under optimal conditions and visible light, the photocatalytic system based on BTNs augmented by H2O2 consumed 1261.17 kWh/m3 of EE for removing more than 90 % of PCs and COD at a treatment cost (t-cost) of 66.84 $/m3 .